The impact of making weight on physiological and cognitive processes in elite jockeys - Dolan, E.; Cullen, S.; McGoldrick, A.; Warrington, G. D. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Purpose: To examine the impact of making weight on aerobic work capacity and cognitive processes in a group of professional jockeys. Methods: Nine male jockeys and 9 age-, gender-, and BMI-matched controls were recruited to take part in two experimental trials, conducted 48 hr apart. The jockeys were asked to reduce their body mass by 4% in the 48 hr between trials, and controls maintained usual dietary and physical activity habits between trials. Aerobic work capacity was assessed by performance during an incremental cycle ergom- eter test. Motor response, decision making, executive function, and working memory were assessed using a computerized cognitive test battery. Results: The jockey group significantly reduced their body mass by 3.6 ± 0.9% (p < .01). Mean urine specific gravity (Usg) readings increased from 1.019 ± 0.004-1.028 ± 0.005 (p < .01) following this reduction in body mass. Peak work capacity was significantly reduced between trials in the jockey group (213 ± 27 vs. 186 ± 23 W, p < .01), although VO2peak (46.4 ± 3.7 vs. 47.2 ± 6.3 ml·kg·min-1) remained unchanged. No changes were identified for any cognitive variable in the jockey group between trials. Conclusion: Simulation of race day preparation, by allocating a weight that is 4% below baseline body mass caused all jockeys to report for repeat testing in a dehydrated state, and a reduction in aerobic work capacity, both of which may impact on racing performance.